2011
DOI: 10.1074/jbc.m111.282772
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Receptor Signaling Is Required for Fibronectin-induced Matrix Metalloproteinase 9 Production by Human and Murine Macrophages and Is Attenuated by the Arhgef1 Molecule

Abstract: Background: Arhgef1Ϫ/Ϫ macrophages exhibit exaggerated matrix metalloproteinase (MMP) 9 production when cultured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Intriguingly, previous studies have shown that ARHGEF1-deficient mice spontaneously develop pulmonary pathology characterized by key features of emphysema with increased expression and activity of MMPs, airspace enlargement, and decreased lung elastance (Hartney, Brown et al 2010). Of additional interest was the finding that macrophages lacking ARHGEF1 produce increased levels of MMP-2, -9 and -12 upon adhering to fibronectin (Hartney, Gustafson et al 2011) suggesting that ARHGEF1 is critical for the ability of immune cells to properly sense cues derived from the extracellular matrix, a parameter that could be of great relevance to RA pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, previous studies have shown that ARHGEF1-deficient mice spontaneously develop pulmonary pathology characterized by key features of emphysema with increased expression and activity of MMPs, airspace enlargement, and decreased lung elastance (Hartney, Brown et al 2010). Of additional interest was the finding that macrophages lacking ARHGEF1 produce increased levels of MMP-2, -9 and -12 upon adhering to fibronectin (Hartney, Gustafson et al 2011) suggesting that ARHGEF1 is critical for the ability of immune cells to properly sense cues derived from the extracellular matrix, a parameter that could be of great relevance to RA pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…While Fn is less active than its degradation products, it is also able to induce the expression of metalloproteinases in some contexts. In this regard, Fn increases MMP-9 production in human and murine macrophages [199]. Furthermore, Fn induces MMP-2 expression in human prostate cancer cells [200].…”
Section: Fn-fs Modulate the Upa System And Induce Mmp Expressionmentioning
confidence: 94%
“…TXA2 is synthesized in response to platelet activation by, for example, collagen-receptor glycoprotein VI (GPVI) stimulation and is an autocrine and paracrine active molecule acting as a positive-feedback mediator in platelets amplifying the initial signals to ensure the rapid activation (Li et al, 2010). The TXA2 receptor (TP) is also expressed on macrophages and monocytes where it is involved in regulation of matrix metalloproteinase 9 (Hartney et al, 2011) and tissue factor expression (Eligini et al, 2006;Gaussem et al, 2005).…”
Section: Introductionmentioning
confidence: 99%